Gambaran Hasil Pemeriksaan Pewarnaan Diff-Quik pada Swab Mukosa PSK - Hermawan, Rizal Aditya; Sabban, Indra Fauzi; Angelina, Lisa; Kusnidar, Gilang; Wahyuni, Ismiy Noer; Rokim, Moch. Abdul (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
High-risk commercial sex workers (CSWs) are highly susceptible to sexually transmitted infections (STIs), which often manifest in the oral mucosa. Therefore, a rapid, accurate, and affordable oral health screening method at the primary healthcare level is needed to detect cellular changes early. The purpose of this study was to describe the morphology of epithelial cells and the quality of oral mucosal swabs obtained using Diff-Quik staining in CSWs. This study used a descriptive observational study of 20 CSW respondents, with a total of 80 samples taken using the buccal mucosal swab technique and stained using the Diff-Quik method. The results showed that 81.25% of the samples had good staining quality, with clear nuclear and cytoplasmic details. Although the cell morphology was generally normal, pathological findings in the form of cellular damage (vacuolization and pyknosis) and inflammatory cell infiltration (PMN leukocytes) were found in 27.5% of the samples. The conclusion of this study is that Diff-Quick staining is very effective for rapidly assessing oral cytology, which indicates inflammation and cell damage in CSWs in the region.